2004
DOI: 10.1200/jco.2004.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, Behavioral, and Immune Changes After a Psychological Intervention: A Clinical Trial

Abstract: Purpose-This randomized clinical trial tests the hypothesis that a psychological intervention can reduce emotional distress, improve health behaviors and dose-intensity, and enhance immune responses.Patients and Methods-We studied 227 women who were surgically treated for regional breast cancer. Before adjuvant therapy, women completed interviews and questionnaires assessing emotional distress, social adjustment, and health behaviors. A 60-mL blood sample was drawn for immune assays. Patients were randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
425
2
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 367 publications
(460 citation statements)
references
References 77 publications
18
425
2
10
Order By: Relevance
“…The institutes included sessions discussing intervention adaptation, another departure from typical CE programs. Adaptation was included as it was anticipated that trainees would have different patient populations than the newly diagnosed breast cancer patients with which the BBI was validated [22]. Moreover, implementation of an innovation (such as an EBT) typically requires some adaptation of the innovation, the setting, or both [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The institutes included sessions discussing intervention adaptation, another departure from typical CE programs. Adaptation was included as it was anticipated that trainees would have different patient populations than the newly diagnosed breast cancer patients with which the BBI was validated [22]. Moreover, implementation of an innovation (such as an EBT) typically requires some adaptation of the innovation, the setting, or both [33].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized clinical trial (RCT: BBI plus assessment vs. assessment only) accrued consecutive patients (n=227) with newly diagnosed regional (stage II or III) breast cancer. Tests of the efficacy [22][23][24][25] demonstrated significant reductions in distress and improvements in social adjustment, health behaviors (diet, smoking cessation), treatment adherence, health, and enhanced T cell immunity for participants in the BBI arm. Tests of the disease endpoint of the trial-recurrence-found that patients in the BBI arm had reduced risk of breast cancer recurrence [hazard ratio (HR)=0.55, p=0.034] [23].…”
Section: Introductionmentioning
confidence: 99%
“…Patients were randomized to receive either psychosocial intervention or assessment only. As predicted, patients in the intervention group demonstrated psychological and behavioral improvements over time [16]. T cell proliferation in response to phytohemagglutinin (PHA) and concavalin A (con A) remained stable or increased for patients in the intervention group, whereas both responses declined for patients in the assessment group.…”
Section: Introductionmentioning
confidence: 66%
“…It has been extensively validated in studies of patients with diverse serious illnesses, including cancer [8,[13][14]. Significant reductions in cancer-associated psychological distress can be achieved with psychosocial interventions aimed at decreasing stress levels, strengthening social support networks, and improving coping and life management skills [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation